2013
DOI: 10.3892/or.2013.2810
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor is negatively correlated with the methylation-mediated transcriptional repression of miR-375 in human prostate cancer cells

Abstract: Androgen receptor (AR) plays a critical role during the development and progression of prostate cancer in which microRNA miR-375 is overexpressed and correlated with tumor progression. Although DNA methylation is a key mechanism for the repression of gene expression, the relationship between AR and the expression or the hypermethylation of miR-375 is unknown. In this study, we found that AR-positive prostate cancer (PCa) cells showed high expression levels and hypomethylation of the miR-375. In contrast, AR-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 30 publications
(34 reference statements)
3
33
0
Order By: Relevance
“…Finally, our gene set enrichment analysis analysis revealed that miR-375 is positively correlated with androgen signalling in multiple tumor data sets (Supplementary Figure 9). A molecular mechanism that potentially underpins this association was recently elucidated by Chu et al, 42 who demonstrated that the androgen receptor (AR) indirectly promotes miR-375 transcription by suppressing DNA methylation of its promoter. Thus, miR-375 may also serve as a proxy for AR activity and PSA levels, which are themselves prognostic in prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, our gene set enrichment analysis analysis revealed that miR-375 is positively correlated with androgen signalling in multiple tumor data sets (Supplementary Figure 9). A molecular mechanism that potentially underpins this association was recently elucidated by Chu et al, 42 who demonstrated that the androgen receptor (AR) indirectly promotes miR-375 transcription by suppressing DNA methylation of its promoter. Thus, miR-375 may also serve as a proxy for AR activity and PSA levels, which are themselves prognostic in prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Chu et al found that there existed the negative correlation between AR and total DNMT activity, indicating that DNMTs are such responder for this process and can be negatively controlled by AR. 13) In addition, ART could induce the marked sustained increase of [Ca 2+ ] i , and subsequently triggered the apoptosis of prostatic cancer cells. 24) While DNMT3b resulted in the increase in apoptosis of prostatic cancer cells, DNMT3b should be positively related to ART, which was approved by our analysis of DNMTs expression of PCa tumor and PCa cells that both of the expression and the catalytic activity of DNMT3b were upregulated when AR was restrained in the presence of ART.…”
Section: Discussionmentioning
confidence: 99%
“…12) Interestingly, DNMTs activity can be negatively regulated by AR in human prostate cancer cells. 13) Therefore, the present study used the prostatic cancer cells 22rv1 and investigated the effects of ART on the growth in mice and cell viability and apoptosis in vitro, and the expressions of AR and DNMTs as well, aiming to demonstrate the role of AR and it regulated DNMTs in anti-PCa action of ART.…”
mentioning
confidence: 99%
“…Of these differentially methylated sequences detected by MCAM, we selected four genes (GAS6, GAD2, MAP6, and CNN3) for validation on the basis of several criteria: a P-value less than 0.01, only probes located in the CGIs, probes with a frequency of 70% in one group and less than 30% in the other, gene function, and confirmation that the gene was methylated in the AR ¡ SCPC patient samples analyzed by the Illumina 450K array. Additionally, we chose to validate TMPRSS2 solely on the basis of results from the Illumina arrays because of gene function and previous reports of methylation status in AR-negative prostate cancer cell lines 23 We then used pyrosequencing to quantify the methylation levels of these genes in the xenograft samples (Fig. 2B).…”
Section: Differences In Dna Methylation Profiles Between Armentioning
confidence: 99%